Identification of a Polyketide Synthase Required for Alternariol (AOH) and Alternariol-9-Methyl Ether (AME) Formation in Alternaria alternata - Saha, Debjani; Fetzner, Ramona; Burkhardt, Britta; Podlech, Joachim; Metzler, Manfred; Dang, Ha; Lawrence, Christopher; Fischer, Reinhard (PLOS ONE, 2012)
Alternaria alternata produces more than 60 secondary metabolites, among which alternariol (AOH) and alternariol-9-methyl ether (AME) are important mycotoxins. Whereas the toxicology of these two polyketide-based compounds has been studied, nothing is known about the genetics of their biosynthesis. One of the postulated core enzymes in the biosynthesis of AOH and AME is polyketide synthase (PKS). In a draft genome sequence of A. alternata we identified 10 putative PKS-encoding genes. The timing of the expression of two PKS genes, pksJ and pksH, correlated with the production of AOH and AME. The PksJ and PksH proteins are predicted to be 2222 and 2821 amino acids in length, respectively. They are both iterative type I reducing polyketide synthases. PksJ harbors a peroxisomal targeting sequence at the C-terminus, suggesting that the biosynthesis occurs at least partly in these organelles. In the vicinity of pksJ we found a transcriptional regulator, altR, involved in pksJ induction and a putative methyl transferase, possibly responsible for AME formation. Downregulation of pksJ and altR caused a large decrease of alternariol formation, suggesting that PksJ is the polyketide synthase required for the postulated Claisen condensations during the biosynthesis. No other enzymes appeared to be required. PksH downregulation affected pksJ expression and thus caused an indirect effect on AOH production.